Unlearning Love: Defying Colonial Knowledge in Bell Hooks's All About Love: New Visions - Giri, Pradip Raj (Tribhuvan University Journal, 2024)
This paper is a critical reading of bell hooks's All About Love: New Visions. It explores the concept of Love, which she defines in various aspects of people’s life, going beyond the established idea or definition of love. She also challenges conventional ideas of Love and the ways people practice it, giving or taking it. The traditional understanding of Love reinforces norms that restrict how people feel, express, or define Love. This research investigates the colonial roots that influence contemporary definitions of Love and specifically examines how colonial ideologies have shaped relationships, gender roles, and social expectations. Employing a qualitative approach, this study draws on theoretical frameworks, including Maldonado-Torres' concept of ‘On the Coloniality of Being,’ Tuck and Yang's notion of “Decolonization is Not a Metaphor,” and Aurora Levins Morales' concept of "the Historian as Curandera" to analyze colonial knowledge embedded within modern interpretations of Love. Hence, the research shows that redefining the concept of Love actively confronts colonial ideologies by promoting a decolonized and restorative view of Love, which encourages more inclusive and genuine relationships. In conclusion, this study suggests that unlearning colonial interpretations of Love pave the way for more inclusive and holistic approaches to Love and societal norms.